Delphi-Technique as a Method for Research on Professional Learning - Harteis, Christian (Methods for Researching Professional Learning and Development)

Kompetenzerwerb auf der Schulstation: Eine Mixed-Methods-Replikationsstudie - Goller, Michael; Steffen, Bianca; Lau, D. (Professionalisierung der Gesundheitsberufe. Berufliche und hochschulische Bildung im Spiegel aktueller Forschung)

Essays on Industrial Organization and Networks: Retail Bundling, Exclusive Dealing, and Network Disruption - Endres-Fröhlich, Angelika Elfriede

Methods for Researching Professional Learning and Development

Decision Support Ecosystems: Deﬁnition and Platform Architecture - Kirchhoff, Jonas; Weskamp, Christoph; Engels, Gregor (Decision Support Systems XII: Decision Support Addressing Modern Industry, Business, and Societal Needs)
Decision support systems are crucial in helping decision makers to quickly identify optimal business decisions in increasingly volatile and complex business environments. However, the ideal DSS for one decision maker may not optimally address the requirements for decision support of another decision maker. This is due to differences between decision makers in business goals, regulatory restrictions or availability of resources such as data. By using a suboptimal DSS, decision makers risk implementing suboptimal decision recommendations which endanger the success of their business. This presents DSS developers with the challenge to implement a customizable DSS which can be tailored to the individual requirements for decision support of a single decision maker. In order to address this challenge, we suggest a decision support ecosystem in which DSS developers, decision makers and other domain experts collaborate using a shared platform to provide and combine reusable decision support services into a tailored DSS. The contribution of our paper is twofold: First, we define the concept of a decision support ecosystem with respect to existing digital business ecosystems and discuss expected benefits and challenges. Second, we present a reference architecture for a shared platform supporting the realization of a decision support ecosystem. We demonstrate our contributions in the example application domain of regional energy distribution network planning.

Requirements-Based Composition of Tailored Decision Support Systems - Kirchhoff, Jonas; Weskamp, Christoph; Engels, Gregor (Human-Centered Software Engineering)
Corporate decision makers have individual requirements for decision support influenced by business goals, regulatory restrictions or access to resources such as data. Ideally, decision makers could quickly create tailored decision support systems (DSS) themselves which optimally address their individual requirements for decision support. Although service-oriented architectures have been proposed for DSS customization, they are primarily targeting trained software developers and cannot immediately be adapted by decision makers or domain experts with little to no software development knowledge. In this paper, we therefore motivate an assisted process-based service composition approach which can be used by non-developers to create tailored DSS. For assistance during service composition, we contribute a meta-model for the formalization of both decision support requirements and functionality of decision support services. Models created according to the meta-model can be used to detect mismatches between a decision maker’s requirements for decision support and services selected in the service composition representing a DSS. Furthermore, the formalizations may even be used for automated service composition given a decision maker’s decision support requirements. We demonstrate the expressiveness of our meta-model in the domain of regional energy distribution network planning.

Amplified steady state bifurcations in feedforward networks - von der Gracht, Sören; Nijholt, Eddie; Rink, Bob (Nonlinearity)
We investigate bifurcations in feedforward coupled cell networks. Feedforward structure (the absence of feedback) can be defined by a partial order on the cells. We use this property to study generic one-parameter steady state bifurcations for such networks. Branching solutions and their asymptotics are described in terms of Taylor coefficients of the internal dynamics. They can be determined via an algorithm that only exploits the network structure. Similar to previous results on feedforward chains, we observe amplifications of the growth rates of steady state branches induced by the feedforward structure. However, contrary to these earlier results, as the interaction scenarios can be more complicated in general feedforward networks, different branching patterns and different amplifications can occur for different regions in the space of Taylor coefficients.
Keywords: Applied Mathematics; General Physics and Astronomy; Mathematical Physics; Statistical and Nonlinear Physics

Influence of Screw Design on Fiber Breakage of Glass Fiber Reinforced Polypropylene in the Injection Molding Process - Moritzer, Elmar; Bürenhaus, Franziska Isabelle (37th International Conference of the Polymer Processing Society (PPS))

Characterization of Fiber Dust Resulting from Recycling of Carbon Fiber-Reinforced Thermoplastics (CFRP) and Their Cell Toxicity - Hopp, Matthias; Tölle, Lisa; Monsé, C.; Rosenkranz, N.; Haibel, N.; Walter, D.; Bünger, J.; Westphal, G. (Journal of Material Science and Chemical Engineering)

Multimaterial Injection Moulding of Thermosets and Elastomers - Moritzer, Elmar; Scheiermann, Denis; Bellusova, Denisa; Klie, Benjamin; Giese, Ulrich (ScienceBG)

Spritzgießen hochtemperaturbeständiger Baugruppen aus Duromeren und Elastomeren - Moritzer, Elmar; Scheiermann, Denis; Bellusova, Denisa; Klie, Benjamin; Giese, Ulrich (Kunststoffland NRW)

Institutionen der Medienpädagogik: Schule und Medien - Herzig, Bardo (Handbuch Medienpädagogik)

Messtechnische Ermittlung der Strukurintensität bei spritzgegossenen, faserverstärkten Kunststoffen - Moritzer, Elmar; Netzband, Dennis; Ujma, Andreas

Moodle in der Hochschullehre: Struktur durch HTML-Code - Fiege, Amanda Sophie; Pape, Stefan (#MoodleKannMehr – nicht nur im Distanzunterricht!)

Protest von Rechts? Strategien neurechter bzw. rechtspopulistischer Akteure zur Aneignung diskursiver Positionen des Widerstands im sogenannten 'Dritten Reich' - Markewitz, Friedrich (Protest, Protestieren, Protestkommunikation)

Quantum Dot Molecule Devices with Optical Control of Charge Status and Electronic Control of Coupling - Bopp, Frederik; Rojas, Jonathan; Revenga, Natalia; Riedl, Hubert; Sbresny, Friedrich; Boos, Katarina; Simmet, Tobias; Ahmadi, Arash; Gershoni, David; Kasprzak, Jacek; Ludwig, Arne; Reitzenstein, Stephan; et al. (Advanced Quantum Technologies)
Keywords: Electrical and Electronic Engineering; Computational Theory and Mathematics; Condensed Matter Physics; Mathematical Physics; Nuclear and High Energy Physics; Electronic; Optical and Magnetic Materials; Statistical and Nonlinear Physics

Neue Polymerwerkstoffe - Der Schlüssel für die Industrialisierung - Klippstein, Sven Helge

Authentic Englishes.nrw – Developing and Using Interactive Teaching and Learning Materials on Varieties of English - Pape, Stefan; Fiege, Amanda Sophie; Mindt, Ilka (Selected Papers from the 2021 Conference of the German Association for the Study of English)

Theorie-Praxis-Relationierung im Praxissemester: Die Perspektive der Mentor*innen. Eine explorative Studie - Caruso, Carina; Neuweg, Georg Hans; Wagner, Marlene; Harteis, Christian (Zeitschrift für Erziehungswissenschaft)
In der Mehrheit der deutschen Bundesländer ist ein Langzeitpraktikum (Praxissemester) Bestandteil der Lehramtsstudiengänge. Es zielt insbesondere darauf, Theorie und Praxis miteinander in Beziehung zu setzen. Trotz der gewichtigen Rolle, die den Mentor*innen dabei zugeschrieben wird, ist deren Perspektive noch wenig untersucht. Die empirisch auffindbaren Unterschiede in der Betreuung Studierender könnten u. a. auf unterschiedliche Vorstellungen von der Beziehung zwischen Theorie und Praxis seitens der Mentor*innen zurückzuführen sein. Diese Vorstellungen interessieren in der im Folgenden dargestellten explorativen Interviewstudie, deren Daten einer strukturierenden Inhaltsanalyse unterzogen wurden. Nachstehenden Forschungsfragen wird nachgegangen: 1) Sind die Mentor*innen auf die Aufgabe der Verknüpfung von Theorie und Praxis vorbereitet? 2) Werden in den Erzählungen der Mentor*innen zu gelingenden und misslingenden Betreuungserfahrungen Theorie-Praxis-Relationierungsfiguren sichtbar, wenn ja, welche und zeigen sich Bemühungen der Verknüpfung von Theorie und Praxis? 3) Werden in den Erzählungen der Mentor*innen zur eigenen Lerngeschichte Theorie-Praxis-Relationierungsfiguren sichtbar, wenn ja, welche und welche relative Rolle spielt das Ausbildungswissen aus Sicht der Mentor*innen für die Entwicklung ihres Könnens? 4) Welches Wissensverständnis der Mentor*innen zeigt sich in den Transkripten und welche Relevanz wird Wissen im Vergleich zu Erfahrung, Reflexion von Erfahrung und Persönlichkeit zugeschrieben? Es zeigt sich, dass die Mentor*innen das Theorie-Praxis-Verhältnis in den Gesprächen selten thematisieren, die Begriffe „Wissen“ und „Können“ synonym verwenden und der Erfahrung für die Entwicklung von Können eine höhere Relevanz beimessen als dem didaktischen und pädagogischen Ausbildungswissen.
Keywords: Lehrer*innenbildung; Mentoring; Praxissemester; Professionalisierung; Theorie-Praxis-Relationierung

Öffnung der Blackbox Hochschullehre durch kollaborative Autoethnografie - Autor:innengruppe , AEDiL (Ethnografie der Hochschule)